Bindeelementer i danske nominalkomposita - Szubert, Andrzej (Folia Scandinavica Posnaniensia, 2009)
The aim of the article is to present the phenomenon of linking elements in Danish nominal compounds. The article presents the possible linking elements being used in Danish nominal compounds and tries to show the mechanisms in the choice of a particular linking element. There is also a discussion, whether we have to do with linking elements or inflexion in Danish nominal compounds. As a part of the conclusion some statistics on the linking elements in Danish nominal compounds is shown.